2018
DOI: 10.1007/s00122-018-3087-5
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput genotyping-by-sequencing facilitates molecular tagging of a novel rust resistance gene, R 15 , in sunflower (Helianthus annuus L.)

Abstract: A novel rust resistance gene, R , derived from the cultivated sunflower HA-R8 was assigned to linkage group 8 of the sunflower genome using a genotyping-by-sequencing approach. SNP markers closely linked to R were identified, facilitating marker-assisted selection of resistance genes. The rust virulence gene is co-evolving with the resistance gene in sunflower, leading to the emergence of new physiologic pathotypes. This presents a continuous threat to the sunflower crop necessitating the development of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…Sunflower wild relatives have been valuable sources for genetic improvement of elite sunflower germplasm (Seiler, Qi, & Marek, ), and have been used to introgress cytoplasmic male sterility, resistance against biotic and abiotic stresses, herbicide resistance and fatty acid modifications (as reviewed in Warburton et al, ). H. argophyllus is a diploid species (2n = 34) and has been exploited for the introgression of fertility restorer genes (Havekes, Miller, & Jan, ), and resistance to rust (Ma, Song, Markell, & Qi, ; Qi et al, ), downy mildew (Ma et al, ), and charcoal rot (Shehbaz et al, ). It has also been found to be highly diverse for traits related to resistance against drought, heat and sucking pests (Hussain et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sunflower wild relatives have been valuable sources for genetic improvement of elite sunflower germplasm (Seiler, Qi, & Marek, ), and have been used to introgress cytoplasmic male sterility, resistance against biotic and abiotic stresses, herbicide resistance and fatty acid modifications (as reviewed in Warburton et al, ). H. argophyllus is a diploid species (2n = 34) and has been exploited for the introgression of fertility restorer genes (Havekes, Miller, & Jan, ), and resistance to rust (Ma, Song, Markell, & Qi, ; Qi et al, ), downy mildew (Ma et al, ), and charcoal rot (Shehbaz et al, ). It has also been found to be highly diverse for traits related to resistance against drought, heat and sucking pests (Hussain et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…H. argophyllus is a diploid species (2n = 34) and has been exploited for the introgression of fertility restorer genes (Havekes, Miller, & Jan, 1991), and resistance to rust (Ma, Song, Markell, & Qi, 2018;Qi et al, 2016), downy mildew (Ma et al, 2017), and charcoal rot (Shehbaz et al, 2018). It has also been found to be highly diverse for traits related to resistance against drought, heat and sucking pests .…”
Section: Discussionmentioning
confidence: 99%
“…The first rust resistant cultivar was developed in Canada in 1954, and subsequently, two rust resistance genes (R genes), R 1 and R 2 , were discovered [3,4]. Since then, a total of 13 rust R genes, R 1 -R 5 , R 10 -R 15 , P u6 , and R adv , have been reported from sunflower and its wild relatives, which are summarized in Ma et al [5]. Major gene resistance against biotrophic pathogens, such as rust, is generally unstable and nondurable, due to the emergence of virulent races in pathogen populations.…”
Section: Introductionmentioning
confidence: 99%
“…Friskop et al [8] identified 29 NA P. helianthi races from 238 single-pustule isolates collected from fields in 2011 and 2012. Among the 13 rust R genes, only seven, R 11 , R 12 , R 13a , R 13b , R 14 , R 15 , and R 16 , remain effectively resistant to all P. helianthi races identified in the USA [5,[9][10][11][12]. In some areas, although a single gene confers resistance to the existing pathogen population, large-scale use of this gene results in the breakdown of resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation